Punishing disease: HIV and the criminalization of sickness - Hoppe, Trevor (University of California Press, 2018)
Introduction : Punishment : AIDS in the shadow of an American institution -- Controlling Typhoid Mary -- "HIV stops with me" -- The public health police -- Making HIV a crime -- HIV on trial -- Victim impact -- Conclusion : Punishing disease -- Appendix 1 : methods : on the anatomy of a social problem -- Appendix 2 : list of bills